The Impact of Curcumin, Resveratrol, and Cinnamon on Modulating Oxidative Stress and Antioxidant Activity in Type 2 Diabetes: Moving beyond an Anti-Hyperglycaemic Evaluation - Michalina Banaszak; Ilona Górna; Dagmara Woźniak; Juliusz Przysławski; Sławomira Drzymała-Czyż (MDPI AG, 2024)
Research indicates that up to half of the population resorts to dietary supplements for managing diseases such as type 2 diabetes rather than changing their nutritional habits. These supplements not only aim to have an anti-hyperglycaemic effect but also seek to reduce oxidative stress to prevent diabetes complications. This systematic literature systematic review aims to evaluate the efficacy of curcumin, resveratrol, and cinnamon in modulating oxidative stress and antioxidant activity in individuals with type 2 diabetes. Data were collected from PubMed, Web of Sciences, and Scopus databases regarding the impact of curcumin, resveratrol, and cinnamon on total antioxidant capacity (TAC), malondialdehyde (MDA), tumour necrosis factor α (TNF-α), interleukin 6 (IL-6), and high-sensitivity C-reactive protein (hs-CRP) levels for this review. Effect sizes for each study were calculated using Cohen's or Hedges's d coefficient. Parameters of oxidative stress and inflammatory status, such as TAC, MDA, TNF-α, IL-6, and hs-CRP, improved following phytochemicals. Additionally, curcumin, resveratrol, and cinnamon exhibited regulatory effects on carbohydrate metabolism by reducing glucose, insulin, and glycated haemoglobin concentrations and lipid metabolism by lowering total cholesterol (TC), low-density lipoprotein (LDL), and triglycerides (TG) and increasing high-density lipoprotein (HDL). Incorporating curcumin, resveratrol, and cinnamon into diets may be beneficial for maintaining organism homeostasis and improving metabolic control in individuals with type 2 diabetes. However, the conflicting results reported in the literature highlight the need for further detailed investigations into the effectiveness of phytochemical use for type 2 diabetes.